Penerapan Model Pembelajaran Make a Match untuk Meningkatkan Kemampuan Kognitif Anak di TK GMIM Bukit Zaitun Manado - Mieke F. Tiwow (Peneliti.net, 2021)
This study aims to describe an increase in learning outcomes by applying the Make A Match learning model to early childhood at GMIM Kindergarten Bukit Zaitun Manado. This study used classroom action research using the Kemmis and Taggart models which consisted of four stages, namely: the planning, implementation/action, observation and reflection stages. By carrying out two cycles, the research results were obtained as follows: (1) There was an increase in learning outcomes before treatment and after applying the make a match learning model in learning activities with the theme of plants.